Development of DC Microgrid Integrated Electric Vehicle Charging Station With Fuzzy Logic Controller - Hadero, Mathewos; Khan, Baseem (Frontiers in Energy Research, 2022)
The development of a direct current (DC) microgrid for charging stations is proposed in this paper. Electric energy infrastructure is not modernized enough and it is difficult to fully depend on the energy obtained from grids. As a result, integrating renewable energy (solar), grids, and energy storage is critical. The capacity of the system to handle predicted and sudden changes (in production and consumption) and disruptions while preserving consistency in the performance of service to consumers is critical to the dependability of renewable energy integration. As a result, this work employs a fuzzy logic controller to integrate a DC microgrid. The proposed maximum operating voltage of this DC microgrid charging station is 500V. Power flow management using a fuzzy logic controller keeps voltage within the expected range with standard voltage deviation and improves the response time (1.645ms). Moreover, the operating costs per year of the proposed system are also being investigated.